UPAYA MENINGKATKAN MOTIVASI MENULIS KARYA SATRA MELALUI SINIAR - Ihtiyatul Muhakimah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The purpose of this study is to determine the factors that cause literary writers to find it difficult to carry out writing activities and the role of podcast as a medium that helps literary writers to overcome writing difficulties so that their motivation and enthusiasm for writing rises again. The method in this research is descriptive qualitative to explain or interpret systematically and accurately about the factors that cause the decline in the motivation of literary writers and the role of narration in overcoming the problems that faced by literary writers. There are 100% of the 20 research samples who have difficulty in writing literary works. Some of these difficulties include (1) 80% difficulty getting inspiration, (2) 75% lack of vocabulary so that it is difficult to choose the right words, (3) 70% lack of knowledge in using PUEBI (General Guidelines for Indonesian Spelling) rules correctly, (4) 75% difficulty getting ideas or topics, and (5) 50% difficulty in publishing literary works. There are several roles of podcast that can help overcome the difficulty of writing literary works, as followed (1) helping in finding inspiration, (2) finding ideas or topics, (3) adding vocabulary, and (4) publishing literary works. Apart from the roles previously mentioned, there are actually many roles that can help minimize the problems faced by literary writers.